Editorial Note (American Journal of Islam and Society, 2022)
The four articles, two review essays, various book reviews, and obituary contained in this issue all revolve around contestations of Islamic authority. Notably, two of these articles are drawn from the AJIS symposium on Maqāṣid whose first set of essays were featured in the previous issue (38:3-4) dedicated to the topic.These four articles and the remaining elements of the issue foreground contemporary contestations of Islamic authority. Read together, they also offer a set of terms for thinking productively about its contours, limits, affordances, and possibilities.